Tolstoy's Art and Thought, 1847-1880 - Orwin, Donna Tussing, 1947- (Book collections on Project MUSE., 1993)
""My aim is to present Tolstoy's work as he may have understood it himself, "" writes Donna Orwin. Reconstructing the intellectual and psychic struggles behind the masterpieces of his early and middle age, this major study covers the period during which he wrote The Cossack's, War and Peace, and Anna Karenina. Orwin uses the tools of biography, intellectual and literary history, and textual analysis to explain how Tolstoy's tormented search for moral certainty unfolded, creating fundamental differences among the great novels of the ""pre-crisis"" period. Distinguish.